The python 3 standard library by example - Hellmann, Doug (Pearson, 2018)
The Python 3 Standard Library contains hundreds of modules for interacting with the operating system, interpreter, and Internet-all extensively tested and ready to jump-start application development. Now, Python expert Doug Hellmann introduces every major area of the Python 3.x library through concise source code and output examples. Hellmann's examples fully demonstrate each feature and are designed for easy learning and reuse. You'll find practical code for working with text, data structures, algorithms, dates/times, math, the file system, persistence, data exchange, compression, archiving, crypto, processes/threads, networking, Internet capabilities, email, developer and language tools, the runtime, packages, and more. Each section fully covers one module, with links to additional resources, making this book an ideal tutorial and reference